2020
DOI: 10.1109/ojcoms.2020.2969751
|View full text |Cite
|
Sign up to set email alerts
|

Coverage Enhancement for NLOS mmWave Links Using Passive Reflectors

Abstract: The future 5G networks are expected to use millimeter wave (mmWave) frequency bands to take advantage of large unused spectrum. However, due to the high path loss at mmWave frequencies, coverage of mmWave signals can get severely reduced, especially for non-line-of-sight (NLOS) scenarios as mmWave signals are severely attenuated when going through obstructions. In this work, we study the use of passive metallic reflectors of different shapes/sizes to improve 28 GHz mmWave signal coverage for both indoor and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 18 publications
6
89
0
Order By: Relevance
“…This setup corresponds to a scenario in which S is employed in the millimeter-wave frequency band, and its size, 2L, corresponds to, approximately, the diagonal of a two-dimensional surface of size 1 m 2 . This is compatible and in agreement with other recent papers and experimental activities [13], [16], [21].…”
Section: Numerical Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This setup corresponds to a scenario in which S is employed in the millimeter-wave frequency band, and its size, 2L, corresponds to, approximately, the diagonal of a two-dimensional surface of size 1 m 2 . This is compatible and in agreement with other recent papers and experimental activities [13], [16], [21].…”
Section: Numerical Resultssupporting
confidence: 94%
“…Similar results have been obtained in [15]. In [16], the power measured from passive reflectors in the millimeter-wave frequency band is compared against ray tracing simulations. By optimizing the area of the surface that is illuminated, it is shown that a finite-size passive reflector can act as an anomalous mirror.…”
Section: Introductionsupporting
confidence: 71%
“…In [78], the authors study, through experimental measurements, the power scattered from passive reflectors that operate in the millimeter-wave frequency band. Also, the authors compare the obtained results against ray tracing simulations.…”
Section: E Path-loss and Channel Modelingmentioning
confidence: 99%
“…The path loss and small-and large-scale fading must be addressed to comprehend the propagation characteristics of indoor and outdoor locations for wireless communication channels. A study [167] has obtained remarkable results for NLOS mmWave environment by using passive reflectors. Another study [168] is performed for an NLOS indoor localization system by proposing an RF-ECHO method that attains high accuracy in long-distance indoor NLOS environments.…”
Section: Nr Mmwave (24-100 Ghz)mentioning
confidence: 99%